2016
DOI: 10.1097/gme.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of Chinese herbal medicine granules for the treatment of menopausal symptoms by stages

Abstract: The DZQE formula improves the quality of life for menopausal women, especially for those with vasomotor symptoms during the whole menopausal period. The DZQE and EZ combination formula is effective only on perimenopausal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…There are multiple treatment options other than MHT proposed by different authors for menopausal symptoms. Fu et al conducted a randomized trial on usage of Chinese herbal medicine among patients with menopause and they found significant improvement in vasomotor symptoms after 8 weeks of usage of herbal granules [20]. In another study by Nourozi et al, Soy milk ingestion was compared with low fat cow milk.…”
Section: Number Of Patients Percentagementioning
confidence: 99%
“…There are multiple treatment options other than MHT proposed by different authors for menopausal symptoms. Fu et al conducted a randomized trial on usage of Chinese herbal medicine among patients with menopause and they found significant improvement in vasomotor symptoms after 8 weeks of usage of herbal granules [20]. In another study by Nourozi et al, Soy milk ingestion was compared with low fat cow milk.…”
Section: Number Of Patients Percentagementioning
confidence: 99%
“…Hence, ovarian dysfunction during perimenopause leads to reduced production of E 2 and abnormal lipid metabolism. Previous studies have demonstrated that the Chinese herbal medicine preparation Jiawei Qing'e Fang reduces hot flushes, improves menopausal symptoms and has a potential advantage in reducing triglyceride levels (Fu et al 2016). Therefore, the discovery of drugs that are effective against ovarian dysfunction and dyslipidaemia will be a groundbreaking discovery in the pursuit of effective management to improve ovarian function and lipid metabolism (Yoshihisa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This underscores the need to improve ovarian function and attenuate the morbidity and mortality associated with lipid dysregulation in perimenopausal women (Sanada et al 2002;Ho et al 2010). Available reports indicate that the DZQE formula improves the quality of life for menopausal women, especially for those with hot flush symptoms thorughout the menopausal period (Fu et al 2016). Both in vivo and in vitro experiments have proved the efficacy of natural compounds, suggesting that studies on natural compounds that improve oestrogen levels make substantial impact.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations